Perencanaan Memiliki Anak pada Wanita dengan HIV Positif di Kota Semarang - Nastiti Bandari Pratiwi; Zahroh Shaluhiyah; Antono Suryoputro (Jurnal Promosi Kesehatan Indonesia, 2019)
Background: Pregnant women with HIV positive is potential risk to transmit the virus to their infants. Prevention Mother to Child Transmittion (PMTCT) program is a solution for HIV women if they want to have children. However, most pregnant women detected HIV positive when they have been pregnant for more than 6 months through Provider initiated test and counselling (PITC). On the other hand, the data shows that the increasing number of HIV positive women who have been willing to have children.  This research aims to identify and examine the factors influence the plan of having children among HIV-positive women who access HIV treatment in Kariadi Hospital Semarang. Method: This study employs a quantitative research design with cross sectional approach, followed by qualitative study to explore the feeling and attitudes of women with HIV positive to plan of having children. There were 31 women involved in this study, selected with the criteria of fertile women HIV positive who have been taking antiretroviral therapy in Kariadi Hospital and willing to participate in this study. Qualitative data collected from two women who has been planning to have children. Quantitative data were analyzed by univariate, Chi-Square and multiple logistic regression. Whilst, qualitative data employ content analysis.Results: There were 16% of women with HIV positive who have been intending to have children in this study. The rest have not planned it because they worried if their pregnancy and delivery could transmit HIV to their infants. CD4 cell count, ARV access and women’s attitudes have significant correlation to the intention of having children among women with HIV positive. Comprehensive information about PMTCT and ARV were needed to deliver to fertile women with HIV positive.